THE FEATURES OF LEXICAL TRANSFORMATIONS IN THE PROCESS OF TRANSLATION (Philological Studies, 2019)
This article is devoted to the problem of translation as an energy process, the result of which is the interpreter's desire to preserve the ethnoenergetic charge of the source language in the translating language by changing of the language code. The material of Russian-language translations from English and German languages demonstrates the difference between the method proposed here and the methods adopted in translation studies.
Keywords: energy, translation, equivalence, ethnic language, phraseological unit, original language, translating language